Toward a circular Kuznets curve: integrating circular economy and life cycle assessment into industrial waste modeling - Kanwal, Qudsia; Xu, Guochang; Al-Ghamdi, Sami G. (Frontiers in Sustainability, 2026)
Decoupling economic growth from industrial waste generation remains a central challenge in sustainability transitions. While the Environmental Kuznets Curve (EKC) suggests that environmental pressures may decline after an income threshold, our analysis of Saudi Arabia's Industrial Solid Waste (ISW) from 2012–2024 shows a statistically robust N-shaped trajectory: ISW rises with GDP, stabilizes, and then rebounds at higher income levels. Tapio elasticity results further indicate persistent expansive coupling, confirming that economic expansion alone does not alleviate ISW pressures. A structured uncertainty assessment evaluates the effects of data gaps, interpolation, and model sensitivity to structural breaks. To address the observed rebound, we develop a Circular Economy-adjusted EKC (CE-EKC) framework that links recycling, industrial symbiosis, EPR mechanisms, and landfill taxation with LCA-based indicators capable of shifting EKC turning points and flattening rebound slopes. The findings underscore the need for coordinated CE policy packages to align industrial growth with long-term sustainability objectives under Vision 2030.